Determination of γ-oryzanol, Phenolic total content, and (2,2-difenil-1-picrylhydrazyl) Radical Scavenging Activity in Different Varieties of Rice (Oryza sativa) in Yogyakarta, Indonesia - Erna Prawita Setyowati; Andayana Puspitasari Gani (Majalah Obat Tradisional, 2018)
In Indonesia, beras (Oryza sativa) has become the main ingredient in natural beauty products such as masks, scrubs, and cold powder. γ-oryzanol and phenolic compounds are the major components in beras that have many benefits, one of which as antioxidants. This study aims to determine the content of γ-oryzanol and total phenolic compounds in different beras cultivars in the area of Yogyakarta. The leveling was done by a TLC-densitometry method and Folin Ciocalteu. The results showed that the largest γ-oryzanol content found in red beras was 0.0843% by weight of the sample. The highest total phenolic content was found in red beras as much as 1.92% by weight of the sample. The antioxidants activity IC50 Red Beras is 0.591.